Gestión administrativa en el cyber j & j de la ciudad de Babahoyo - Villena Vilche, Yeraldi Yelena (2022)
The purpose of this case study is to determine the irregularities due to administrative mismanagement that does not allow the correct functioning of the activities carried out in the cyber, by virtue of which it has been projected as the main objective to analyze the administrative management of the cyber J&J from the city of Babahoyo, to contribute with the possible solution that this microenterprise needs to guarantee a quality service that will serve to attract more clients; The inductive and descriptive method has been applied in addition to reinforcing the approach to the problem, with different theoretical sources from experts in the field on the effect that the correct application of administrative management has on the success of any business; and based on this and on the results obtained from the techniques and instruments used, such as the observation analysis, the interview together with its questionnaire applied to the owner of the cyber and the survey addressed to the business workers; It has been shown that most of its employees do not have knowledge in the matter of administrative management, this also occurs because its owner does not hire trained personnel to help boost their business.